Compound Astragalus and Salvia miltiorrhiza extract inhibits hepatocellular carcinoma progression via miR-145/miR-21 mediated Smad3 phosphorylation. (1st March 2019) - Wu, Chao; Chen, Weiyang; Fang, Meng; Boye, Alex; Tao, Xiangming; Xu, Yuanyuan; Hou, Shu; Yang, Yan
Abstract: Ethnopharmacological relevance: Compound Astragalus and Salvia miltiorrhiza extract (CASE), containing astragalosides, astragalus polysaccharide extracted from Astragalus membranaceus (Fisch.) Bge. and salvianolic acids from Salvia miltiorhiza Bge., has been found to inhibit hepatocarcinogenesis via mediating transforming growth factor-β (TGF-β)/Smad signaling, especially Smad3 phosphorylation. The crucial interaction between microRNA-145/microRNA-21 (miR-145/miR-21) and Smad3 phosphorylation is implicated in the pathogenesis and progression of hepatocellular carcinoma (HCC). However, effects of CASE on HCC progression involved in the expression of miR-145/miR-21 and their interaction with Smad3 phosphorylation downstream of TGF-β/MAPK/Smad pathway remain unclear. This study addressed above questions using in vitro (HepG2 cells) and in vivo (Xenografts of nude mice) models of HCC. Materials and methods: In vivo [Diethylnitrosamine (DEN)-induced HCC in rats] and in vitro [TGF-β1 -stimulated HepG2 cells] models of HCC were established and co-administrated using graded doses/concentrations CASE (60, 120, 240 mg/kg used in rats; 20, 40, 80 µg/ml used in HepG2 cells), miR-145 and miR-21 were measured. HepG2 cells were transfected with miR-145 antagomir, miR-21 agomir and Smad3C/L plasmids (Smad3 EPSM, Smad3 3S-A and Smad3 WT related to up-regulated expression of pSmad3C, pSmad3L and pSmad3C/3L respectively) and then treated by CASE (80 µg/ml). Similarly, HepG2 cell xenografted nude mice were administered with miR-145 antagomir, miR-21 agomir and CASE (310 mg/kg); Smad3 WT, Smad3 EPSM and Smad3 3S-A plasmids stably transfected HepG2 cell lines were constructed respectively and their xenografted nude mice were established, and then treated by CASE (310 mg/kg). Cell proliferation, migration, apoptosis, tumor growth and histopathologic characteristics of xenografts were assessed; also, domain-specific Smad3 phosphorylation isoforms (pSmad3C/pSmad3L), activated MAPKs (pERK1/2, pJNK1/2, pp38) and miR-145, miR-21 were measured. Results: CASE up-regulated miR-145 while down-regulated miR-21 expression in both rats with DEN-induced HCC and TGF-β1 -stimulated HepG2 cells; CASE inhibited cell migration, proliferation and tumor growth while facilitated cell apoptosis in TGF-β1 -stimulated HepG2 cells and xenografts of nude mice with miR-145 antagomir/miR-21 agomir treatment via increasing miR-145 and facilitating miR-145 modulated pSmad3L→pSmad3C signaling switch while decreasing miR-21 and inhibiting miR-21 modulated MAPK-dependent Smad3L phosphorylation. Also, up-regulated pSmad3C enhanced inhibited effect of CASE on tumor growth and facilitated effect of CASE on cell apoptosis involved in increased miR-145 while decreased miR-21 expression, however, inverse phenomena were observed when up-regulated pSmad3L. Conclusion: Our results suggest that CASE inhibits HCC progression via mediating the interaction of miR-145/miR-21 and Smad3 phosphorylation, especially miR-145/miR-21 mediated Smad3 phosphorylation, which maybe provides an important theoretical foundation for CASE's anti-HCC therapy used for patients in a near future. Graphical abstract: